Pengaruh Good Corporate Governance, Ukuran Perusahaan, Dan Profitabilitas Terhadap Manajemen Laba Pada Perusahaan Sektor Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Permatasari, Ria Anjelli; Armin, Rini; Verlandes, Yuliasnita (Philosophiamundi, 2024)
The purpose of this study is to investigate and identify the impact of Good Corporate Governance (managerial ownership, institutional ownership, foreign ownership, independent board of commissioners, audit committee), firm size, and profitability on earnings management practices. The studied population consists of transportation and logistics sector companies listed on the Indonesia Stock Exchange during the period 2019-2023, totaling 23 companies. The research sample comprises 5 companies observed over 5 years, from 2019 to 2023, using purposive sampling method. Data used are sourced from the companies' annual reports as secondary data. The data analysis methods applied include classic assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS software version 22. The research findings indicate that variables of Good Corporate Governance (managerial ownership, institutional ownership, foreign ownership, independent board of commissioners, and audit committee) do not have a significant influence on earnings management. On the other hand, firm size is proven to have an impact on earnings management practices, while profitability variable does not show a significant influence on earnings management.